2020
DOI: 10.1007/s13762-020-02762-5
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity and functional diversity in soil in different cultivation systems

Abstract: The aim of the work was to evaluate the impact of use of conventional and organic cultivation systems on selected parameters of microbial activity in the soil under wheat, barley and oat cultivation. Microbiological, biochemical, enzymatic and metabolic activities were analyzed during three seasons over 3 years in soil. The more beneficial effect of organic cultivation was reflected in the increase in bacterial growth, the intensification of the nitrification and higher activity of all analyzed enzymes. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
1
8
0
3
Order By: Relevance
“…We evidence that the mycobiome biodiversity is dependent on both the cultivation system (intercropping mixture/maize monoculture) and the season (spring, summer, and autumn). This confirms the results reported by He et al (2017) , Sommermann et al (2018) , and Jezierska-Tys et al (2020) , which suggested that both cultivation systems and vegetation phenology may be responsible for the differentiated seasonal variations of fungal diversity. Li et al (2019) , indicate that the fungal richness and diversity in acidic red forest soils in summer and autumn are higher than in spring.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We evidence that the mycobiome biodiversity is dependent on both the cultivation system (intercropping mixture/maize monoculture) and the season (spring, summer, and autumn). This confirms the results reported by He et al (2017) , Sommermann et al (2018) , and Jezierska-Tys et al (2020) , which suggested that both cultivation systems and vegetation phenology may be responsible for the differentiated seasonal variations of fungal diversity. Li et al (2019) , indicate that the fungal richness and diversity in acidic red forest soils in summer and autumn are higher than in spring.…”
Section: Discussionsupporting
confidence: 91%
“…Biodiversity loss is one of the most serious global environmental problems caused by human activities ( Fuchs et al, 2021 ). Fungi in the soil play the role of saprophytes, reducers, and symbionts and have an important function in the generation of crop yields ( Klaubauf et al, 2010 ; Jezierska-Tys et al, 2020 ). Therefore, knowledge of their presence and structure in agricultural soils is desirable.…”
Section: Discussionmentioning
confidence: 99%
“…Within the soil microbiome, arbuscular mycorrhizal fungi (AMF) play a key role in plant nutrition due to their capacity to improve plant mineral uptake ( Smith and Smith, 2011 ; Rouphael et al, 2015 ). This could explain differences in mineral composition of plant food in dependence of the farming system since microbiological and enzymatic activities are higher in organically farmed soil ( Jezierska-Tys et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…LCA is a highly versatile methodology, which finds application in different production sectors, it can be used for the evaluation of entire industrial systems (Zhao et al 2018;Sabeen et al 2019) or individual products (Peters et al 2017;Cano Londoño et al 2019), it can involve the study of new technologies (Lacirignola et al 2017;van der Giesen et al 2020) or the improvement of existing ones (Mohammadi and South 2017;Neri et al 2018); moreover, it can also be applied both on an industrial (Cespi et al 2016;Piccinno et al 2018) and laboratory (Ricciardi et al 2017;Tsapekos et al 2019) scale to address sustainability in various fields. Its use has naturally reached also agricultural studies, with a particular focus on biological systems, as shown by the numerous recent works carried out on the subject (Quirós et al 2015;Clark and Tilman 2017;Brockmann et al 2018;Trinh et al 2020;Avadí 2020;Jezierska-Tys et al 2020).…”
Section: Methodsmentioning
confidence: 99%